SUBSTANCE USES, DEPRESSION, SOCIAL ANXIETY AND ACADEMIC ACHIEVEMENT AMONG UNIVERSITY STUDENTS - Jalil, Rakhshanda; Akhtar, Shammem (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The current study aims to explore Substance use, Depression, Social Anxiety and Academic Achievement among University Students. The observation of substance use, Depression, Social Anxiety and educational Achievement is so essential in this cutting-edge era. The sample for the present study of 225 (95 male and 130 female) changed into decided on from exceptional universities the purposive sampling technique. A correlational research design and convenient sampling technique were to measure study variables. Adult, Academic Performance Rating Scale, depression and social anxiety scale used where to check substance use, and Drug Use Questionnaire (DAST 28) were applied. The observed findings suggest that a large tremendous courting among materials makes use of, melancholy, social tension among university students. Multiple linear regression and t-tests on sample analyses for inferential facts were additionally done to check the hypotheses. The findings confirmed a large sample uses drugs and faces mental health issues but a value of (-1.01) shows a small distinction between male and female substance use.  Similarly, the t-value of -1.04 suggests a small distinction between male and female depression levels. The p-value of 0.298 showed that this distinction isn't statistically large. No distinction was found in depression ranges among male and female university students. The t-value of -1.43 represents a distinctly small distinction in social anxiety rankings among male and female students. The consequences suggest largely terrible courting among substance use and educational achievement among university students. Results additionally suggest depression and social anxiety are terribly correlated with academic achievements. Findings found that there are no large variations between male and female university students in phrases of substance use, depression, social anxiety and educational performance amongst university students. The consequences found that substance use of are slight tremendous large predictor of depression among university students. The study focuses on the significance of addressing substance use, melancholy, and social anxiety among students to enhance their academic overall performance and well-being.D.O.I. https://zenodo.org/records/10825116